2021
DOI: 10.1155/2021/4906360
|View full text |Cite
|
Sign up to set email alerts
|

Track Behavior and Crash Risk Analysis of Passenger Cars on Hairpin Curves of Two-Lane Mountain Roads

Abstract: Hairpin curves are often employed in alignment layout and an important feature that identifies dangerous driving conditions for mountain roads. However, driving behaviors at hairpin curves remain ambiguous. Field driving tests were conducted in this study on one two-lane mountain road with 11 hairpin curves. Vehicle-mounted equipment was utilized to collect track and lateral distance between the wheels and the lane markings under naturally driving conditions. Track morphology and patterns, risks, and road cras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The evaluation of road alignment consistency based on operating speed is critical to improving highway safety design and road service quality [23]. The lateral amplitude versus speed model was constructed, as speed was the primary factor affecting the trajectory oscillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of road alignment consistency based on operating speed is critical to improving highway safety design and road service quality [23]. The lateral amplitude versus speed model was constructed, as speed was the primary factor affecting the trajectory oscillation.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers try to investigate the properties of vehicle trajectory oscillation to help comprehend lane departure. Yu et al [23] demonstrated the consistency between vehicle trajectory and speed. They found a positive correlation between trajectory offset and traveling speed in curved sections.…”
Section: Vehicle Trajectory Oscillation and Lane Keepingmentioning
confidence: 99%
“…Previous studies have explored methods for classifying trajectories on curved segments, encompassing both single-indicator-based and mixed classifcation methods. Te single-indicator-based classifcations, such as trajectory radius [24], lane departure [25], and curve-cutting position [26], ofer specifc advantages such as efective sideslip risk description, simplicity and practicality, and utilization of turning characteristics, respectively. On the other hand, mixed classifcation [27], exemplifying patterns such as cutting, swinging, drifting, correcting, and normal and ideal behavior, provides a systematic categorization of vehicle trajectories on curved segments, being widely utilized despite its limitations in precise indicator defnition and potential overlap in trajectory categories.…”
Section: Introductionmentioning
confidence: 99%